2011
DOI: 10.1002/lt.22242
|View full text |Cite
|
Sign up to set email alerts
|

Spur cell anemia as a cause of unconjugated hyperbilirubinemia after liver transplantation and its resolution after retransplantation

Abstract: TO THE EDITORS:Spur cell anemia is a type of hemolytic anemia that can develop in patients with advanced liver disease (especially alcoholic cirrhosis). 1 Spur cells, the extreme form of acanthocytes, have a unique morphology with multiple thornlike projections that vary in length and width. 2 These projections are thought to form because of a decreased ratio of phospholipids to cholesterol in red blood cell membranes. 3,4 Spur cell anemia should be suspected in patients with a known history of severe liver di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…Vassiliadis et al reported a 25-day median survival rate in the 9 patients with SCA, and only one patient, who had undergone liver transplantation, had survived after 1 year [12]. To our knowledge, there have been 24 case reports on 26 patients with SCA since 1983 including our case (Table 3) [13,14,16,19,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. On reviewing these cases, the average age was 42.6 years old, and 14 (53.8%) of the 26 patients were men.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Vassiliadis et al reported a 25-day median survival rate in the 9 patients with SCA, and only one patient, who had undergone liver transplantation, had survived after 1 year [12]. To our knowledge, there have been 24 case reports on 26 patients with SCA since 1983 including our case (Table 3) [13,14,16,19,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. On reviewing these cases, the average age was 42.6 years old, and 14 (53.8%) of the 26 patients were men.…”
Section: Discussionmentioning
confidence: 67%
“…As for treatment, abstinence from alcohol is required to avoid the progression of alcoholic liver cirrhosis. Liver transplantation remains the only curative treatment for reversing SCA [13][14][15][16][17], and very few attempts have been made for treatment without liver transplantation. Flunarizine is reported to impair the morphological abnormality of red blood cells, and two cases of SCA treated by flunarizine are reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of liver transplant in the management of SCHA is not well defined. Resolution of SCHA with liver transplant has been described in single‐patient case reports 7–10 and a two‐patient case series, 11 however, MELD exception points are not routinely considered for patients with SCHA, despite evidence suggesting a worse prognosis 12…”
Section: Introductionmentioning
confidence: 99%
“…The role of liver transplant in the management of SCHA is not well defined. Resolution of SCHA with liver transplant has been described in single-patient case reports [7][8][9][10] and a two-patient case series, 11 however, MELD exception points are not routinely considered for patients with SCHA, despite evidence suggesting a worse prognosis. 12 The goal of this multicenter cohort study was to address these knowledge gaps by defining the hematologic, hepatic, and prognostic impacts of SCHA as well as describing the outcomes of liver transplant in this rare complication of cirrhosis.…”
mentioning
confidence: 99%